Associations between Paternal Co-residence and Child Health among African American Children. (March 2023) - Barcelona, Veronica; Flowers, Ambre; Caceres, Billy A.; Crusto, Cindy A.; Taylor, Jacquelyn Y.
We investigated the associations between paternal co-residence and asthma, obesity, and blood pressure among children aged 3–5 years. Mother/child dyads ( N  = 250) self-identified as African American or Black. Mothers reported on father's co-residence and child's asthma diagnosis. Height, weight, and blood pressure were measured. Regression models were used to examine paternal co-residence with child health outcomes (i.e., asthma, obesity, and blood pressure). Confounders included maternal and child age, child sex, maternal smoking, and insurance status. Children who lived with their fathers were less likely to have asthma ( OR  = 0.39, 95% CI 0.18–0.79), though this association was not significant after adjustment for confounders ( aOR  = 0.47, 95% CI 0.22–1.01). Paternal co-residence was not significantly associated with child obesity ( aOR  = 0.78, 95% CI 0.35–1.73), systolic (β = 0.57, SE  = 1.2, p  = .64), or diastolic (β = 1.91, SE  = 1.0, p  = .07) blood pressure. More research is necessary to understand the diversity of family living situations and how they affect child health.